Engraving in the House of Austria during the First Half of the 16th Century: A Visual Tool at the Service of the Propaganda System - Sosa Rubio, Carlos Jesús (Eikón / Imago, 2024)
The rise of the printing press during the first half of the 1500s ran parallel to the development of reprographic techniques that not only facilitated the multiplicity and dissemination of images, but also their use as the backbone of any propaganda system, in favor or against the civil or ecclesiastical power. All this, moreover, sharpened by a heterogeneous system of political-territorial organization, the empire, in which the transversality of the image would enjoy a power and agglutinating capacity from which the sphere of reading and writing was still kept away. These pages reflect on the use that the Habsburg dynasty made, throughout this period, of engraving techniques such as xylography or etching, analyzing as well how the diffusion of a series of engravings, that of Nikolas Hogenberg on the procession after the coronation of Charles V in Bologna (1530), allowed this historical event to be reflected in different materials and spaces, both in Spain and in Italy. Imagocentrism, for the reasons stated, acquired a strong impulse in this incipient modernity.